Decision-Making for The Selection of Vegetable Suppliers for Foods Distributors uses AHP and TOPSIS - Sabhira, Chintya Salwa; Wahyuni, Annisa Tri; Septiani, Winnie; Luis, Martino (OPSI, 2024)
The evaluation of supplier selection is an important aspect that needs to be considered in supply chain management. The best suppliers contribute to a more efficient supply chain system. Companies operating in the food distribution sector are particularly attentive to their suppliers. One of the products that receives significant attention is spinach, a perishable item, making supplier evaluation crucial. This research aims to evaluate the supplier selection of spinach products based on several criteria, such as delivery, quality, price, service, and location. Weighting is done using the Analytical Hierarchy Process (AHP). In this case, assessment or weighting is carried out by distributing questionnaires to three respondents in the field. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method is employed to determine the rankings of each alternative. The results of this study indicate that the price criterion has the highest weight with a weight of 0.39. The recommended selected alternative is alternative 4, with the highest average value (Vi) based on the assessments of three experts. This model proves capable of addressing the issues of supplier selection evaluation, leading to the selection of alternative or supplier 4 as the spinach supplier for the food distribution company.